Axiomatic method and the law - Schuhr, Jan C. (Paper series. Series A, Methodology, logics, hermeneutics, linguistics, law and finance World Congress of Philosophy of Law and Social Philosophy, 2012)
Whether an axiomatic approach to law is possible and useful today has to be perceived as unanswered. Perception of the axiomatic method among lawyers, however, is clouded by misunderstanding. Clarifying them may generate new discussion about the axiomatization of legal theories